Solutions Of Boundary-Value Problems For A System Of Differential Equations Of The Fourth Order With The Method Of Finite Differences - et. al., Olimov Murodillo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper considers a system of fourth-order ordinary differential equations. The system of equations is written in vector form. Computational algorithms are presented using the finite difference method with an error of O(h2). The resulting algebraic equations are solved by the matrix sweep method. Exact and approximate solutions of test problems are given. And also the errors of the considered numerical method are estimated.